STUDY OF THE DEMAND LEVEL FOR SPARE PARTS IN AUTO SERVICE ENTERPRISES - Polvonov Abdijalil Sattarovich (Journals Park Publishing, 2025)
The article presents the results of modeling the need for spare parts using adaptive mathematical models for the formation of the need for spare parts of car service enterprises, the emergence, randomness, and distribution patterns of the need for spare parts during maintenance and repair of vehicles, and forecasting.
Keywords: Car service enterprises, spare parts, mathematical models, technical service, repair, demand, need, time, operational factors, spare parts store, mathematical expectation of distribution, coefficient of relative significance, factor, expert methods, probabilitys